A scoping review of the utility of self-report and informant-report prospective memory measures. Issue 6 (3rd July 2022) - Sugden, Nicole; Thomas, Matt; Kiernan, Michael
ABSTRACT: There has been increased use of self-report prospective memory (PM) scales in recent years, despite uncertainty about their validity. This study reviewed how self-and informant-report PM questionnaires have been used in the assessment of PM. We evaluated relationships between self-report, informant-report, and performance-based PM measures, and the validity of using self-report measures in detecting PM impairments and monitoring intervention outcomes. The scoping review methodology of Arksey and O'Malley (2005 . Scoping studies: Towards a methodological framework. International Journal of Social Research Methodology, 8 (1), 19–32) was used. Database searches yielded 488 published studies that used the Prospective Memory Questionnaire (PMQ), Prospective and Retrospective Memory Questionnaire (PRMQ), Comprehensive Assessment of PM (CAPM), and Brief Assessment of PM (BAPM). The self-report and informant-report measures of PM had weak- to moderate-strength relationships with performance-based PM measures. Some self-report PM scales could detect PM impairments and monitor intervention outcomes, however few studies had investigated this. The findings indicated that self- and informant-report scales measure different constructs to performance-based measures of PM. It is recommended that these scales be used alongside performance-based measures to provide complementary and comprehensive assessments of PM. Further research into assessment of PM using self-report measures will aid assessment and treatment choices.